THE USE OF POP-UP BOOK MEDIA TO IMPROVE GEOMETRY LEARNING OUTCOMES OF GRADE V STUDENTS OF SD QUR'ANI AL-IKHLASH RAPPANG - Zainal, Zaid; Hakim, Abdul; Darwis, Nurhikma (JURNAL EDUSCIENCE, 2024)
The problem in this study is the low learning outcomes of fifth grade students of Qur'ani Al-Ikhlash Rappang Elementary School. The purpose of this study was to determine the improvement of the process and student learning outcomes on geometry material in class V of Qur'ani Al-Ikhlash Rappang Elementary School through the use of pop-up book media. The approach used is a qualitative approach and the type of research is classroom action research (PTK). The implementation of this research action was carried out in 3 cycles starting with pre-action activities, then each cycle consisted of 4 stages which included planning, implementation, observation, and reflection. Data were obtained through observation techniques, learning outcomes tests and documentation. The instruments in this study were observation sheets, learning outcomes tests and documentation. The results showed that in cycle I the results of observations of teacher and student activities in the category of sufficient (C). In cycle II shows the results of teacher activity observations in the good category (B) and student activity observations in the moderate category (C). In cycle III, it showed an increase in the observation results of teacher activities in the good category (B) and the observation results of student activities in the good category (B). The research results related to learning outcomes in cycle I completed students 34.6%. In cycle II, students who completed 57.7%. And in cycle III it increased to 88.4%. It can be concluded that the use of pop-up book media can improve the process and learning outcomes of students.Keywords: Pop-up Book Media, Learning Process, Learning Outcomes and GeometryAbstrak Masalah dalam penelitian ini adalah rendahnya hasil belajar siswa kelas V SD Qur’ani Al-Ikhlash Rappang. Tujuan dalam penelitian ini adalah untuk mengetahui peningkatan proses dan hasil belajar siswa pada materi geometri di kelas V SD Qur’ani Al-Ikhlash Rappang melalui penggunaan media pop-up book. Pendekatan yang digunakan adalah pendekatan kualitatif dan jenis penelitian adalah penelitian tindakan kelas (PTK). Pelaksanaan tindakan penelitian ini dilakukan dalam 3 siklus diawali dengan kegiatan pra tindakan, kemudian pada setiap siklus terdiri dari 4 tahapan yang meliputi perencanaan, pelaksanaan, observasi, dan refleksi. Data diperoleh melalui teknik observasi, tes hasil belajar dan dokumentasi. Instrumen pada penelitian ini adalah lembar observasi, tes hasil belajar dan dokumentasi. Hasil penelitian menunjukkan bahwa pada siklus I hasil observasi aktivitas guru dan siswa dengan kategori cukup (C). Pada siklus II menunjukkan hasil observasi aktivitas guru dengan kategori baik (B) dan observasi aktivitas siswa dengan kategori cukup (C). Pada siklus III menunjukkan peningkatan  hasil observasi aktivitas guru dengan kategori baik (B) dan hasil observasi aktivitas siswa dengan kategori baik (B). Hasil penelitian terkait dengan hasil belajar pada siklus I siswa yang tuntas 34,6%. Pada siklus II, siswa yang tuntas 57,7%. Dan pada siklus III mengalami peningkatan menjadi 88,4%. Dapat disimpulkan bahwa penggunaan media pop-up book dapat meningkatkan proses dan hasil belajar siswa di kelas V  SD Qur’ani Al-Ikhlash Rappang.Kata Kunci: Media Pop-up Book, Proses Belajar, Hasil Belajar dan Geometri